Karakteristik Kekerasan dan Struktur Kristal Cordierite Berbasis Silika Sekam Padi dengan Penambahan Alumina (0, 20, 25, dan 30 wt%) - Nindy Elyta Mawarty; Simon Sembiring; Rudy T.M. Situmeang (Jurnal Teori dan Aplikasi Fisika, 2018)
The synthesis, phase structure and hardness analysis of cordierite ceramic has been done with addition of alumina 0, 20, 25, and 30wt%. Magnesium and alumina from Sigma-Aldrich has been used as raw materials while the silica was obtained from extraction of rice husk used 5% KOH and 10% HCl with sol gel method. This cordierite synthesis used solid state method and sintered at 1200oC for 3 hours. Hardness analysis was determined by Microhardness Tester while the phase structure was determined by X-Ray Diffraction (XRD). Hardness value that obtained for C0, C20, C25, and C30 were 50,03 : 52,44 : 35,69 : and 50,46 kgf/mm2 repeatedly. It was proved that excess alumina will increase hardness value. The XRD patterns revealed that cordierite, corundum, spinel, cristoballite, and periclase were formed in the samplesKarakteristik Kekerasan dan Struktur Kristal Cordierite Berbasis Silika Sekam Padi dengan Penambahan Alumina (0, 20, 25, dan 30 wt%)